2008
DOI: 10.1089/cpb.2007.0010
|View full text |Cite
|
Sign up to set email alerts
|

Internet Use and Loneliness in Older Adults

Abstract: Use of the Internet by seniors as a communication technology may lead to changes in older adult social relationships. This study used an online questionnaire to survey 222 Australians over 55 years of age on Internet use. Respondents primarily used the Internet for communication, seeking information, and commercial purposes. The results showed negative correlations between loneliness and well-being. Multiple regression analyses revealed that greater use of the Internet as a communication tool was associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
216
3
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 323 publications
(233 citation statements)
references
References 10 publications
8
216
3
6
Order By: Relevance
“…Some scholars state that the use of Internet has positive effects on persons and groups as it supports our communicative skills by keeping social communication despite geographic restraints (29). The study carried out by Sum et al (30) reports that social isolation among seniors decreases as the use of Internet as a means of communication increases.…”
Section: Social Isolation Among Internet-using Seniorsmentioning
confidence: 99%
“…Some scholars state that the use of Internet has positive effects on persons and groups as it supports our communicative skills by keeping social communication despite geographic restraints (29). The study carried out by Sum et al (30) reports that social isolation among seniors decreases as the use of Internet as a means of communication increases.…”
Section: Social Isolation Among Internet-using Seniorsmentioning
confidence: 99%
“…A metaanalysis of 40 studies [4] indicated a very small detrimental effect (r=-.05) of Internet use on well-being. Sum et al [5] suggest that the relationship between Internet use and wellbeing is complex, with the Internet having different effects depending on its use.…”
Section: Introductionmentioning
confidence: 99%
“…Using a sample of 500 children, Jackson et al [7] similarly demonstrated the detrimental effects of Internet use for communication purposes (all other uses were associated with greater psychological well-being). The study done by Sum et al [5] brought further intricacy into our understanding of the impact of socio-affective Internet behaviours by finding that a greater use of the Internet as a communication tool with relatives and friends was associated with a lower level of social loneliness. In contrast, a greater use of the Internet to find new people was associated with higher levels of emotional loneliness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…또 이동의 제약이 있는 노인들에게 는 여가참여와 정보교환, 교육에 대한 욕구 충족을 이 루는 데 도움을 주었다 [10]. 노년기의 고립감과 우울감 을 감소시키고 새로운 사회관계를 강화시켜 생활만족 이 향상되었다 [11].…”
unclassified